The relationship between tourism and economic growth among BRICS countries: A panel cointegration analysis - Haroon Rasool; Shafat Maqbool; Md. Tarique (Future Business Journal, 2021)
Tourism has become the world's third-largest export industry after fuels and chemicals, and ahead of food and automotive products. From last few years, there has been a great surge in international tourism, culminates to 7% share of World's total exports in 2016. To this end, the study attempts to examine the relationship between inbound tourism, financial development and economic growth by using the panel data over the period 1995-2015 for five BRICS (Brazil, Russia, India, China and South Africa) countries. The results of panel ARDL cointegration test indicate that tourism, financial development and economic growth are cointegrated in the long run. Further, the Granger causality analysis demonstrates that the causality between inbound tourism and economic growth is bi-directional, thus validates the 'feedback-hypothesis' in BRICS countries. The study suggests that BRICS countries should promote favorable tourism policies to push up the economic growth and in turn economic growth will positively contribute to international tourism.
Keywords: C23; G10; L80; L83; 650; BRICS; Cointegration; Economic growth; Financial development; Inbound tourism; Panel granger causality